Quantitative real-time PCR and high-resolution melting (HRM) analysis for strain-specific monitoring of fluorescent pseudomonads used as biocontrol agents against soil-borne pathogens of food crops. Issue 2 (December 2015) - Martini, Marta; Moruzzi, Serena; Ermacora, Paolo; Loi, Nazia; Firrao, Giuseppe
Abstract: Fluorescent pseudomonads colonizing roots of crop plants and producing antifungal metabolites are regarded as a reliable alternative to chemical fungicides against soil-borne phytopathogens. Key factors in successful pathogen control are presence and activity at the appropriate concentration, time, and place of biocontrol agents. Thus, quantification methods to monitor population dynamics are pivotal to the development of reliable application protocols. Real-time PCR is nowadays the most widespread culture-independent technique for the detection and enumeration of different target sequences. Here, its implementation with high resolution melting analysis as a powerful tool to accurately discriminate microbial inoculants is discussed. Highlights: Biocontrol agents as a reliable alternative to chemical fungicides are presented. Fluorescent pseudomonas and their mechanisms of antagonism are described. Real-time PCR as an established quantitative technique for BCAs is presented. The use of HRM as a powerful tool to distinguish microbial inoculants is proposed. A case study of selection and specific diagnosis of a BCA strain is illustrated.